Intervensi selama kehamilan untuk mencegah kelahiran prematur: Systematic literature review - Tetti Solehati; Hana Giriutami; Meideline Chintya; Siti Haiva Alawiyah; Selvia Nurfauzan; Riftania Aulia Puri; Muhammad Iqbal Assafa; Cecep Eli Kosasih (Holistik Jurnal Kesehatan, 2020)
Interventions during pregnancy to prevent preterm birth: A systematic literature review Background: Premature birth is a major factor that contributes to mortality of newborns globally and impacts long-term to health problems for survivors. Premature births have increased in the last 20 years where the phenomenon is equivalent to 1 in 10 births each year. Therefore, prevention of preterm labor is important given to pregnant women.Purpose: This study aimed to find out effectiveness interventions during pregnancy to preventing preterm birth.Method: The design used literature review, articles were collected using search engines such as Academic Search Complete (EBSCO) as many as 78 articles, CINAHL (EBSCO) 36 articles, Science Direct 593 articles, and PUBMED 55 articles. From the predetermined article criteria, it found 3 articles from 762 that correspond to different interventions, namely consumption of progesterone supplements, cognitive behavior to reduce cigarette smoke exposure, and early detection in pregnant women at high risk of preterm delivery.Results: The result showed that there were 3 interventions in the effort to prevent preterm birth, namely: progesterone supplementation therapy, the intervention to reduce exposure to cigarette smoke in the environment, and identification and management of early detection of fast on pregnant women at high risk of preterm birth.Conclusion and Recommendation: several interventions can use in preventing preterm birth of pregnant women effectively, such as progesterone supplementation, reduction in cigarette smoke exposure in pregnant women, and early detection of pregnancy. Further research is suggested by involving the role of the family in preventing premature birthKeywords: Intervention; Pregnant women; Premature birth; Prevention Pendahuluan: Kelahiran prematur merupakan faktor mayor yang berkontribusi terhadap kematian bayi baru lahir secara global dan berdampak pada masalah kesehatan jangka panjang untuk bayi yang selamat. Kelahiran prematur mengalami peningkatan pada 20 tahun terakhir dimana fenomenanya setara dengan 1 dari 10 kelahiran tiap tahunnya. Oleh karena itu pencegahan persalinan prematur penting diberikan kepada ibu hamil.Tujuan: untuk mengetahui intervensi efektif selama kehamilan dalam mencegah persalinan prematur.Metode: Desain yang digunakan adalah literature review, artikel dikumpulkan menggunakan mesin pencarian seperti Academic Search Complete (EBSCO) 78 articles, CINAHL (EBSCO) 36 articles, Science Direct 593 articles, dan PUBMED 55 articles. Dari kriteria inklusi artikel yang telah ditentukan, ditemukan 3 artikel dari 762 yang sesuai dengan intervensi yang berbeda.Hasil: menunjukan bahwa ada 3 intervensi dalam upaya mencegah kelahiran prematur yaitu: terapi suplementasi progesteron, intervesi pengurangan paparan asap rokok pada lingkungan, dan identifikasi dan penatalaksanaan deteksi dini secara cepat terhadap ibu hamil yang berisiko tinggi lahir prematur.Simpulan dan Saran: Intervensi pemberian suplemen progesteron, pengurangan paparan asap rokok di lingkungan ibu hamil, dan deteksi dini pada kehamilan terbukti efektif dalam mencegah kelahiran prematur pada ibu hamil. Disarankan penelitian lebih lanjut dengan melibatkan peran keluarga dalam mencegah kelahiran prematur.